STUDENTS’ PERCEPTION ON QUIPPER VIDEO AS THE APPLICATION TO LEARN ENGLISH (A Research on the Eleventh Grade of SMAN 2 Makassar) - Dian Farah Fauziyyah; Nurdin Noni; La Sunra (Universitas Negeri Makassar, 2022)
The goal of this research was to find out how students in second grade at SMAN 2 Makassar felt about Quipper Video as an application for learning English. This study is quantitative. Random sampling was utilized to choose 130 students from Science and Social Classes for this investigation. Data collecting methods include questionnaire distribution and interviews. Descriptive analysis was used to examine the data. The findings revealed that students' perceptions of Quipper Video as an application for learning English in second grade at SMAN 2 Makassar were favorable. Finally, students were excited with the Quipper Video program, which the instructor used in the English learning process.